Diversity of native reef fish communities in two protected areas in the Caribbean Sea and its relationship to the invasive lionfish. - Cobián Rojas, Dorka (2018)
Lionfish (Pterois volitans) invaded the Caribbean region with the potential to alter the composition and structure of native coral reef fish communities. The objective of this study was to analyze the diversity indices of these fish communities potentially affected by lionfish predation and to compare with pre-invasion data. The study was undertaken in two Caribbean marine protected areas (MPAs): Guanahacabibes National Park (PNG) in W Cuba and Xcalak Reefs National Park (PNAX) in S Quintana Roo. We carried out visual censuses of fish species in reef habitats during the dry and rainy seasons of the period 2013-2015. For this, nine sites were defined and evaluated using stationary counts. Our results showed higher species richness (43.47 ± 5.14) and mean abundance (0.76 ± 1.25) in PNG than in PNAX (40.22 ± 4.96, 0.19 ± 0.46, respectively). Diversity decreased after the arrival of lionfish in a single site of PNG and in two sites of the PNAX, but apparently, these results are more related to the fishing activity effect than to the lionfish presence. Based on the results and assuming that changes in the native fish communities by lionfish may not yet be detected, we recommend to continue the monitoring community descriptions in order to detect future changes in native fish communities.